2018
DOI: 10.1080/09500693.2018.1452306
|View full text |Cite
|
Sign up to set email alerts
|

How do STEM-interested students pursue multiple interests in their higher educational choice?

Abstract: Interest in science, technology, engineering and mathematics (STEM) has lately received attention in research due to a gap between the number of STEM students and the needs of the labour market. As interest seems to be one of the most important factors in deciding what to study, we focus in the present study on how STEM-interested students weigh multiple interests in making educational choices. A questionnaire with both openended and closed-ended items was administered to 91 STEMinterested students enrolled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
1
13
0
4
Order By: Relevance
“…The interests one wishes to pursue parallel to a programme may therefore influence which interests are pursued in a programme (e.g. Hofer 2010;Vulperhorst et al 2018). Our results illustrate this point further by showing how students carefully balance time spend on interests in and parallel to an educational programme.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…The interests one wishes to pursue parallel to a programme may therefore influence which interests are pursued in a programme (e.g. Hofer 2010;Vulperhorst et al 2018). Our results illustrate this point further by showing how students carefully balance time spend on interests in and parallel to an educational programme.…”
Section: Discussionsupporting
confidence: 52%
“…The process of contrasting interests and deciding what to spend time on likely occurs intuitively also depending on the opportunity structure provided for specific engagements (Bergin 2016). Nonetheless, when confronted with a high-stake decision such as the higher education choice, interests may be weighed more explicitly (Vulperhorst et al 2018).…”
Section: Interests and Choicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the description above, it can be concluded that interest is an attitude of awareness of each individual to do something that moves themselves because there is a sense of pleasure and interest to achieve the desired goal. The level of student interest in learning can be seen and measured by: 1) feelings like pleasure (Krapp & Prentzel, 2011), 2) interests marked by reading and learning mathematics, learning without coercion, and recording mathematics lessons (Paszkowska-rogacz & Yıldız, 2015) , 3) attention that is in the form of focus in learning mathematics (Vulperhorst, Wessels, Bakker, & Akkerman, 2018) and 4) student involvement which includes activeness in participating in the learning process and doing assignments (Mumba, Mbewe, & Chabalengula, 2015) Learning outcomes that are often seen are learning achievements. Nitko & Brookhart (2011) revealed that achievements are students' knowledge, skills and abilities that have been developed as a result of learning.…”
Section: Introductionmentioning
confidence: 99%